Pharmaceutical care in patients with gastric cancer treated with capecitabine: A randomized clinical trial - Patrícia Kaiser Pedroso Cava; Camille Nigri Cursino; Larissa Dos Santos Sebould Marinho; Ana Clara Duarte Dos Santos; Ariela Dutra Norberto De Oliveira; Larissa Rodrigues Nascimento; Vanessa Cristiane Da Silva Ferreira; Dulce Helena Nunes Couto; Jessica Pronestino De Lima Moreira; Thaísa Amorim Nogueira; Selma Rodrigues De Castilho; Sabrina Calil-Elias (Journal of Oncology Pharmacy Practice, 2026)
Introduction Cancer poses a major challenge to global health, impacting individuals, communities and societies worldwide. A significant proportion of global morbidity and mortality from neoplasms is accounted for by gastrointestinal tumors, due to their high incidence and lethality. Capecitabine, an oral antineoplastic agent, has brought advances in treatment, but requires caution regarding adherence and adverse events. In this context, it is believed that pharmaceutical care can significantly contribute to optimizing therapy and promoting better clinical outcomes. Objective The aim of this study is to assess the advantages of pharmaceutical care for patients with gastric cancer who are being treated with capecitabine. Methods A multicentre, prospective, longitudinal study was conducted with patients with gastric cancer using capecitabine. Patients were randomised into two groups, namely control (pharmaceutical guidance) and intervention (pharmaceutical care). Sociodemographic, clinical, and therapeutic data were collected, and adverse events were identified, classified and analysed, with impacts such as dose suspension or reduction, emergencies, hospitalisations and use of additional drugs being considered. Quality of life was assessed before and after treatment. Results Thirty-one patients were selected, 16 of whom were in the intervention group. This group completed more treatment cycles, although it had a higher number of adverse events, with less severity. All patients who received pharmaceutical care were adherent to their treatment. In contrast, patients who did not receive pharmaceutical care had more suspensions and dose reductions. They also had a significant worsening of overall functional capacity. In addition, their symptoms such as nausea, vomiting, and diarrhea were aggravated. In the intervention group, however, there was an improvement in these symptoms. Conclusion The study highlights the importance of pharmaceutical care in capecitabine treatment, especially in the management of adverse events, treatment adherence and promotion of quality of life. Despite the small sample size, the results reinforce the role of the pharmacist in the care of these patients and indicate the need for further studies with larger samples.